Development of Physics Learning Media Based-Mobile Learning Using Adobe Flash CS6 at Muhammadiyah University of Makassar (Jurnal Pendidikan Fisika, 2021)
This research is motivated by the fact that physics learning content based on mobile learning can be accessed widely and most students have cellphones, but it has not been widely used to increase student enthusiasm in learning physics. Physics Learning Media Based on Mobile Learning is an effort to solve this problem. One of them is by Development of Physics Learning Media-Based Mobile Learning Using Adobe Flash CS6. This study aimed to determine the development of learning media products based on mobile learning using adobe flash CS6 and to examine the the feasibility of learning media based on mobile learning using Adobe Flash CS6 at Muhammadiyah University of Makassar. This type of research was a research and development starting from the defining stage (define), the design stage (design), and the development stage (develop). This mobile learning-based physics learning media was tested for validity by 2 experts of media, and tested for its effectiveness by 33 students. The results achieved were the m-learning media products that used the adobe flash CS6 application with validity criteria that were relevant, consistent and have practical usability, as well as effective implementation. These instructional media products can be used by teaching staff and students in higher education. as well as effective implementation. These instructional media products can be used by teaching staff and students in higher education. as well as effective implementation. These instructional media products can be used by teaching staff and students in higher education.